THE RELATIONSHIP BETWEEN AGRICULTURAL RAW MATERIALS AND OIL PRICE: AN EMPIRICAL ANALYSIS - Govdeli, Tuncer (Economics of Agriculture, 2022)
The motivation of this study is to investigate the relationship between the price of agricultural raw materials and the real exchange rate of the USA and the price of crude oil. For this purpose, annual data from 1990 to 2020 were used. In the study, the cointegration relationship and the elasticity coefficients of the variables were estimated with the help of ARDL bounds test. In addition, the causality relationship was determined with the help of the Granger test. According to the results obtained, it was concluded that there is a cointegration relationship in the models established for agricultural raw materials. In addition, the elasticity coefficient of oil price was found to be positive. According to the Granger causality analysis results, a one way causality relationship from oil price to agricultural raw materials was determined. We present some policy implications based on our findings in this study.